2015
DOI: 10.3109/09637486.2015.1024204
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofLactobacillus plantarumNCU116 on loperamide-induced constipation in mice

Abstract: Lactobacillus plantarum, as a probiotic, has many functional properties in human intestinal tract. This study examined the effects of L. plantarum NCU116 on loperamide-induced constipation in a mouse model. Loperamide (5 mg kg(-1)) was injected subcutaneously to induce constipation. Animals were divided to five groups: normal group, constipation group, constipation plus three doses of L. plantarum NCU116 groups (NCU116-L, 10(7) CFU/mL; NCU116-M, 10(8) CFU/mL; NCU116-H, 10(9) CFU/mL; respectively). Mice were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 34 publications
5
58
0
Order By: Relevance
“…A similar trend of change was observed in HHPD + atropine model test, however, the data failed to reach significant difference, perhaps due to limited sample size ( n  = 8 in each group). The result was consistent with the microscopic observation after H&E staining, which also supported that EXQ effectively increased the integrity of colonic mucosa as compared to the vehicle group [29]. …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A similar trend of change was observed in HHPD + atropine model test, however, the data failed to reach significant difference, perhaps due to limited sample size ( n  = 8 in each group). The result was consistent with the microscopic observation after H&E staining, which also supported that EXQ effectively increased the integrity of colonic mucosa as compared to the vehicle group [29]. …”
Section: Discussionsupporting
confidence: 87%
“…Then, the stained slides were mounted in neutral balsam and covered with coverslips [29]. Histopathologic changes were observed under optical microscopy (BX53 Olympus, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of SD rats, constipation was successfully induced by subcutaneous injection of 3-5mg/kg Lop for 3-6 continuous days in most experiments [8]. However, constipation phenotypes such as decreased stool number and weight in ICR mice were observed after oral administration of 5 mg/kg Lop [1516]. In the present study, we attempted to induce constipation in ICR mice derived from three different sources using Lop injection.…”
Section: Discussionmentioning
confidence: 99%
“…Several strains of rodents have been utilized to conduct most experiments in studies of Lop-induced constipation, including SD rats, Wistar rats, Balb/c mice, ICR mice and ddY mice [811121314], although ICR mice have only been used in two studies [1516]. However, most studies conducted to date have used only one strain of one animal species to produce animal models for constipation and to evaluate the anti-constipation activity of drugs and extracts from herbal medicines.…”
mentioning
confidence: 99%
“…13,14 Although the exact mode of action of probiotics and these potential antibiotic alternatives remains elusive, emerging studies have suggested that probiotics and dietary nutrients are capable of not only modulating gut microbiome, but also modulating immunity at local and systemic levels via the gut-brain-endocrine-immune axis; thereby promoting intestinal health and/or preventing diseases such as IBS. 12,13,[15][16][17] Although there have been many studies evaluating the potential use of probiotics in IBS and/or constipation, 18 limited attempts have been made to incorporate probiotics into chocolate to evaluate potential anti-constipation effects.…”
Section: Introductionmentioning
confidence: 99%